The complete mitochondrial genome of the Basidiomycete edible fungus Hypsizygus marmoreus. Issue 2 (3rd July 2018) - Wu, Ying-Ying; Shang, Jun-Jun; Li, Yan; Zhou, Chen-Li; Hou, Di; Li, Jia-Li; Tan, Qi; Bao, Da-Peng; Yang, Rui-Heng
Abstract: The complete mitochondrial genome of the edible fungus Hypsizygus marmoreus was published in this paper. It was determined using Pacbio and Illumina sequencing. The complete mitochondrial DNA (mtDNA) is 106, 417 bp in length with a GC content of 31.74%, which was the fourth large mitogenome in Agaricales. The circular mitogenome encoded 67 protein-coding genes and one ribosomal RNAs (rns). Among these genes, 13 conserved protein-coding genes were determined in the genome, including 6 subunits of NAD dehydrogenase (nad1-4, 4L and 6), three cytochrome oxidases (cox1-3), one apocytochrome b (cob) and three ATP synthases (atp6, apt 8 and apt 9). The phylogenic analysis confirmed that H. marmoreus (Lyophyllaceae) clustered together with Tricholoma matsutake (Tricholomataceae).